2019
DOI: 10.1101/697987
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

VolcanoFinder: genomic scans for adaptive introgression

Abstract: Recent research shows that introgression between closely-related species is an important source of adaptive alleles for a wide range of taxa. Typically, detection of adaptive introgression from genomic data relies on comparative analyses that require sequence data from both the recipient and the donor species. However, in many cases, the donor is unknown or the data is not currently available. Here, we introduce a genome-scan method-VolcanoFinder-to detect recent events of adaptive introgression using polymorp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 136 publications
3
45
0
Order By: Relevance
“…We find that regardless of the types of statistics used, we classify the majority of the genome as neutral, and classify more of the genome as sweep than as adaptive introgression (Tables S12-S15). Importantly, we find that we are able to recapitulate signals of previously-identified regions of adaptive introgression in the CEU population with SURFDAWave, such as BNC2 (Sankararaman et al, 2014;Racimo et al, 2015) and APOL4 (Setter et al, 2019) (Figures S30 and S31). BNC2 is another gene thought to play a role in human skin color determination (Visser et al, 2014), whereas the gene APOL4 is significantly up-regulated in people diagnosed with schizophrenia (Monajemi et al, 2002).…”
Section: Application To Empirical Datasupporting
confidence: 65%
See 2 more Smart Citations
“…We find that regardless of the types of statistics used, we classify the majority of the genome as neutral, and classify more of the genome as sweep than as adaptive introgression (Tables S12-S15). Importantly, we find that we are able to recapitulate signals of previously-identified regions of adaptive introgression in the CEU population with SURFDAWave, such as BNC2 (Sankararaman et al, 2014;Racimo et al, 2015) and APOL4 (Setter et al, 2019) (Figures S30 and S31). BNC2 is another gene thought to play a role in human skin color determination (Visser et al, 2014), whereas the gene APOL4 is significantly up-regulated in people diagnosed with schizophrenia (Monajemi et al, 2002).…”
Section: Application To Empirical Datasupporting
confidence: 65%
“…Adaptive introgression is a complex form of natural selection that produces genetic diversity footprints distinct from typical selective sweeps (Setter et al, 2019). In both selective sweeps and adaptive introgression, diversity generally decreases surrounding the beneficial mutation.…”
Section: Classification Of Selective Sweepsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we move away from the selected site recombination breaks apart these migrant haplotypes, leading to patterns of nucleotide diversity that depend on the migration rate and history of the two populations. If the migration rate is low we should expect an excess of migrant haplotypes at the site of the selective introgression and, if the divergence between the migrant and focal population is high, the so-called "volcano" pattern of diversity (Setter et al, 2019), where diversity is maximized at an intermediate distance from the selected site due to a more balanced presence of both migrant and non-migrant alleles. Evolutionary rescue has been explored theoretically (e.g., Gomulkiewicz and Holt, 1995;Uecker and Hermisson, 2016;Anciaux et al, 2018) and observed repeatedly in both experiments (e.g., Bell and Gonzalez, 2009;Lindsey et al, 2013;Ramsayer et al, 2013) and in host-pathogen systems in nature (e.,g., Wei et al, 1995;Feder et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…[13,27]). However, the specific genetic signature of adaptive introgression and its impact on patterns of genetic variation remains less explored (but see e.g., [33]). There is, therefore, a clear need to develop a theoretical framework to investigate the impacts of adaptive introgression on the genomes of natural populations.…”
Section: Introductionmentioning
confidence: 99%